Pengingkatan Kerapatan Kayu Jabon Melalui Impregnasi Furfuril Alkohol dan Nano-SiO2: The Improvement of Jabon Wood Density Through The Furfuryl Alcohol and Nano-SiO2 - Wahyuningtyas, Irma; Dirna, Fitria Cita (PERENNIAL, 2025)
Jabon (Anthocephalus cadamba Miq.) is a fast-growing wood that is widely utilized by the society as a construction material and furniture making. This study aimed to increase the density of jabon wood through a vacuum pressure impregnation method. Furfuryl alcohol (FA) and nano-SiO2 with three concentrations (0.5%, 0.75%, dan 1%) were used as impregnation additives, with control and FA without nanoparticles as comparisons. Impregnation was initiated with a vacuum (0.5 bar) for an hour, followed by pressure (2.5 bar) for 2 hours. The significant results on the physical properties of jabon wood including weight percent gain (WPG), bulking effect (BE), and density showed the success of the modification treatment through the FA and nano-SiO2 impregnation process with various concentrations, which the wood density increased from 0.60 g/cm3 to 0.94 g/cm3. The composition of FA and 1% nano-SiO2 solution was the best treatment to obtain the highest density in modified jabon wood.